Histopathological Spectrum among Patients Presenting with Adult Onset Nephrotic Syndrome - Sharma, Deepak; Bhusal, Pramod; Maharjan, Chunumila; Ghimire, Madhav (Journal of National Heart and Lung Society Nepal, 2024)
Background: Adult nephrotic syndrome is caused by glomerulopathy that manifests differently in Nepal and other nations. Examining the range of glomerulopathy in individuals over 15 with biopsy-proven nephrotic syndrome, estimating its prevalence and age distribution, and connecting its clinical-pathological features using electron microscopy and immunofluorescence are our objectives. Methods: In our tertiary care hospital, we retrospectively reviewed and analysed 157 renal biopsies of adults with nephrotic syndrome that were performed between January 2021 and August 2024, a period of 3.7 years. Results: There were 157 patients with nephrotic syndrome, 92 of whom were men and 65 of whom were women (1.4 :1). Nephrotic syndrome was most common in the 15–25 age group (24.84%), and it was least common in the 76–85 age group (3.18%). Minimal change disease was the most frequent histological finding among people with nephrotic syndrome (n = 34), followed by MGN (21.01%; n = 33), FSGS (17.19%) (n = 27), IgA Nephropathy (9.55%; n = 15), and amyloidosis (7%; n = 11). MPGN and SLE were similar in 6.30% (n=10), diabetic nephropathy was similar in 5.09% (n=8), and collageno-proliferative glomerulonephritis, tubulointerstitial nephritis, and fibrillary glomerulonephritis were similar in 0.35% (n=1) of histological findings. MGN and MPGN had the highest male predominances (2.3:1 and 2.3:1, respectively), even though fewer patients had the histological diagnostic of MPGN. In SLE, the female predominance was highest (1:9) (M:F). Primary glomerular disease were 78.34%, and secondary glomerular disease were 21.65%. Conclusion: Primary glomerular disease, histologically MCD followed by MGN are the most common cause of NS in adults.